2020
DOI: 10.3389/frvir.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Short-Term Virtual Reality Balance Intervention to Improve Mobility Smoothness in Parkinson's Disease

Abstract: Parkinson's disease (PD) is a neurodegenerative condition that is often associated with movement impairments, such as reduced balance and gait control. Virtual reality (VR) is a promising intervention for enhancing rehabilitation efficiency and may assist in overcoming functional limitations imposed by the disability. The objective of this study was to evaluate the feasibility, safety, and efficacy of a 5-weeks VR intervention in increasing mobility smoothness in participants with PD. Participants were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It was found that smoothness is correlated with motor impairment [31] and with standard clinical measures [32][33][34]. Smoothness is used as a parameter for motor performance evaluation during rehabilitation in post-stroke patients [20], parkinsonian patients [35] and spinal cord injury [36]. In the previous studies, motor recovery was associated with increased smoothness.…”
Section: Discussionmentioning
confidence: 95%
“…It was found that smoothness is correlated with motor impairment [31] and with standard clinical measures [32][33][34]. Smoothness is used as a parameter for motor performance evaluation during rehabilitation in post-stroke patients [20], parkinsonian patients [35] and spinal cord injury [36]. In the previous studies, motor recovery was associated with increased smoothness.…”
Section: Discussionmentioning
confidence: 95%
“…They highlighted that a goal-directed stimulation might not be sufficient. In 2020 Schuch et al 97 evaluated the feasibility, safety, and efficacy of a 5-week VR training program. Twenty-three PD patients were enrolled in different tests: TUG; ten-meter walking (10MWT) and various cognitive functions.…”
Section: Virtual Reality Devicesmentioning
confidence: 99%